2021
DOI: 10.3390/md19080462
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Solubilizing and Concentrating Astaxanthin and Other Carotenoids

Abstract: The valuable marine carotenoid, astaxanthin, is used in supplements, medicines and cosmetics. In this study, crustacyanin, an astaxanthin-binding protein, was used to solubilize and concentrate astaxanthin. The recombinant crustacyanin of European lobster spontaneously formed an inclusion body when it was over-expressed in Escherichia coli. In this study, fusing the NusA-tag to the crustacyanin subunits made it possible to express in a soluble fraction and solubilize astaxanthin in aqueous solution. By cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…The biological availability of AST is limited due to its low aqueous solubility [ 23 , 33 ]. β-cyclodextrin (bCD) solubilized AST 110-fold and thus increased antioxidant activity by up to 7-fold compared to free AST [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological availability of AST is limited due to its low aqueous solubility [ 23 , 33 ]. β-cyclodextrin (bCD) solubilized AST 110-fold and thus increased antioxidant activity by up to 7-fold compared to free AST [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low aqueous solubility (less than 2 µg/mL in pH 6.5 solution) and low stability are also problematic for practical application in humans [ 20 , 21 ]. To solve the disadvantages and problems of AST, various formulations based on drug delivery systems have been investigated [ 22 , 23 , 24 ]. Polyakov and Kispert reported that inclusion complexes based on polysaccharides increase aqueous solubility and photostability [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers prefer to buy shrimp that are light grey in color and turn an intense orange color when cooked [61]. The color of shrimp is due to the accumulation of crustacyanin, which is formed by a protein-astaxanthin complex [62]. During cooking, color changes in crustaceans are closely related to the dissociation of astaxanthin (3,3dihydroxy-β,β'-carotene-4,4 -dione) from its pigment proteins [63].…”
Section: Discussionmentioning
confidence: 99%
“…En zanahoria naranja, se encontró que el gen CYP97A3 es responsable de los altos niveles de acumulación de α-caroteno (Ren et al, 2022). Un valioso carotenoide, la astaxantina (3, 30dihidroxi-β, β-caroteno-4, 40-diona; C40H52O4), actúa como agente protector frente al daño oxidativo de células in vivo porque tiene una alta actividad antioxidante (Hara et al, 2021).…”
Section: β-Caroteno Y Astaxantinaunclassified